Extensional flow-based microfluidic device: deformability assessment of red blood cells in contact with tumor cells - Faustino, Vera (2014)
Red blood cell (RBC) deformability has become one of the important factors to assess blood and cardiovascular diseases. The interest on blood studies have promoted a development of various microfluidic devices that treat and analyse blood cells. Recent years, besides the RBC deformability assessment, these devices are often applied to cancer cell detection and isolation from the whole blood. The devices for cancer cell isolation rely mainly on size and deformability of the cells. However, the examination of deformability of the RBCs mixed with cancer cells is lacking. This study aims at determining the deformation index (DI) of the RBCs in contact with cancer cells using a hyperbolic microchannel which generates a strong extensional flow. The DIs of human healthy RBCs and human RBCs in contact with a tumor cell line (HCT-15, colon carcinoma) were compared by analyzing the flowing RBCs images captured by a high speed camera. The results reveal that the RBCs that were in contact with HCT-15 cells have lower deformability than the normal RBCs.